Social distancing during COVID-19: Effects on daily routine of college students - Fiorentin, Luciano; Beltrame, Vilma (Revista Cuidarte, 2022)
Introduction: In response to the SARS-CoV-2 pandemic, the World Health Organization recommended social distancing as a strategy to mitigate the impacts of the coronavirus disease. Among measures adopted to avoid crowds, universities then switched to virtual education. The objective is to reflect on the influence of social distancing during COVID-19 on the daily routine of health sciences students. Materials and methods: A systematic literature review was conducted by searching on PubMed, MEDLINE, LILACS, bioRxiv, medRxiv, as well as BVS and the World Health Organization site for COVID-19 (WHO COVID-19) databases, using combined descriptors such as “coronavirus infections and health science students” and “COVID-19 and health science students”. A total of 1069 articles were initially found, being later refined to 23 for the study. Results were classified into 1) emotional competence disorder, 2) education, 3) eating, sleep and physical activity, and 4) various kind of impacts with frequent manifestations of anxiety, depression, stress, uncertainty distress and changes in physical activity and sleep habits. Student dropout in virtual programs is about 50% in all cases. Conclusions: Knowing how social distancing influenced the daily routine of college students is important for universities to develop support programs tailored to current reality needs and implement future epidemic preparedness programs, helping reduce possible impacts.How to cite this article: Fiorentin Luciano, Beltrame Vilma. Distanciamento social por Covid 19: repercussão na rotina de universitários. Revista Cuidarte. 2022;13(1):e2093. http://dx.doi.org/10.15649/cuidarte.2093
Keywords: Coronavirus Infections; Pandemic; Student Health; Social Isolation